Conhecimentos acerca do HIV/AIDS entre estudantes universitários: uma revisão integrativa - Baraúna, Yana Celine da Silva (Brasil, 2024)
Introduction: Currently, it is known that all individuals are subject to HIV infection, as it is directly related to a person's sociobehavioral factors, regardless of their sexuality. However, young people, homosexuals, racial and ethnic minorities are the most vulnerable population to STI’s in general. The increase in the incidence of HIV among young Brazilians shows that there may be a high rate of misinformation about the routes of transmission and ways to prevent the virus. Objective: To investigate university students knowledge about HIV prevention and transmission through an integrative review. Method: This is an integrative review of the literature. The study included articles that were freely available, original, and with full text, all from the 2012-2022 period in the Portuguese language, and that answered the guiding question. Duplicate articles that did not address the proposed theme were excluded from the study. Results: The studies selected to compose this review showed a predominance of courses in the health area, and within the courses in the health area, there was a predominance of articles written with nursing students. The various studies have different samples of students, but all conclude some level of ignorance among the ways in which the virus is transmitted. Conclusion: It was possible to analyze the knowledge of academics about HIV/AIDS and, in addition to highlighting the gaps, it was possible to analyze that the level of knowledge changes depending on the period in which the student is.